Programming by steps - Scărlătescu, Raluca Oana (Acta Cybernetica, 2003)
The paper introduces a new method of software analysis, design and programming based on a different implementation of a logical flow: the sequence of steps is memorised in a database table, and each step is linked to a specific function inserted in a library. A main application manages the steps' information and runs the functions, until the steps are finished. The database management system stores the data of the each step and its precedence rules, the functions and their parameters, the static and dynamic values of the parameters, the errors, etc. The paper details the principles of the "Programming by steps", explains the reasons, which originally motivated the development of the method, and defines the principal requisites to build an application system. Future aspects of the implementation, as well as advantages/disadvantages of design, implementing and maintaining the system are stated. The paper includes a comparative analysis between the "Programming by steps" and another two methods of software engineering: the "Rapid Prototyping" and the "Component-based Design". Integrative comments and conclusive remarks axe provided in the conclusion of the paper.